Uncertainty shocks, banking frictions, and economic activity - Dario Bonciani; Björn van Roye (Kiel Institute for the World Economy (IfW), 2013)
In this paper we investigate the effects of uncertainty shocks on economic activity using a Dynamic Stochastic General Equilibrium (DSGE) model with heterogenous agents and a stylized banking sector. We show that frictions in credit supply amplify the effects of uncertainty shocks on economic activity. This amplification channel stems mainly from the stickiness in banking retail interest rates. This stickiness reduces the effectiveness in the transmission mechanism of monetary policy.
Keywords: E32; E52; 330; Uncertainty Shocks; Financial frictions; Monetary Policy; Stochastic Volatility; Perturbation Methods; Third-order approximation